The effect of hypnotic suggestion on labor market attachment, functioning, and cognition after brain injury – a randomized controlled trial - Pedersen, Pernille; Løvshall, Claus; Stapelfeldt, Christina Malmose; Nielsen, Claus Vinther; Lindeløv, Jonas Kristoffer (European Journal of Clinical and Experimental Medicine, 2025)
<h2 class="block-title" style="box-sizing: border-box; font-family: Lato, sans-serif; font-weight: bold; line-height: 1.1; color: #010101; margin-top: 23px; margin-bottom: 11.5px; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Abstract <div class="field-name-field-autorzy-" style="box-sizing: border-box; font-size: 14px; color: #010101; display: inline-block !important; float: left !important; padding: 10px 24px 0px 0px !important; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Introduction and aim. Cognitive impairments after acquired brain injury (ABI) or concussion significantly affect work capacity. While hypnotic suggestion has shown promise in improving working memory and work ability, studies on its long-term effects on labor market attachment and cognition are lacking. The aim of this study was to estimate the long-term effect of hypnotic suggestion on labor market attachment, cognition, and functioning following acquired brain injury or concussion. Material and methods. A randomized controlled trial (RCT) was conducted at a municipal vocational rehabilitation center in Denmark, among 87 patients aged 18 to 62 years who experienced ABI or concussion at least 6 months prior to the first therapy session. The study group were randomized according to the applied intervention: usual care (n=28), hypnosis (n=30) or mindfulness (n=29). Participants underwent baseline and 6-month follow-up assessments involving The Danish Register for Evaluation of Marginalization (DREAM), The Wechsler Adult Intelligence Scale – Fourth Edition (WAIS-IV), Impact on Participation and Autonomy questionnaire (IPA), The Working Memory Questionnaire and Trial Making Test related to working memory and functioning, assessing three dimensions: short-term storage, attention, and executive control. Results. The primary outcome was the average number of weeks employed during the 12–24-month period post-inclusion. The mean number of weeks employed was 32.71 (SD: 22.31) in the usual care group, 35.97 (SD: 21.58) in the hypnosis group, and 32.90 (SD: 22.44) in the mindfulness group. All intervention groups had exhibited a working memory score of around 90, which improved to a range of 91 to 95 at the 6-month follow-up. No significant differences were found between the groups. Conclusion. Brief hypnotic treatment at a municipal vocational rehabilitation center for people with ABI and concussion showed no significant advantage over mindfulness or usual care in labor market attachment, cognition, or family functioning. However, participants in the hypnosis group demonstrated improved social functioning at the 6-month follow-up compared to usual care.